Connecting microscopic structures, mesoscale assemblies, and macroscopic architectures in 3D-printed hierarchical porous covalent organic framework foams - Mohammed, Abdul Khayum; Usgaonkar, Saurabh; Kanheerampockil, Fayis; Karak, Suvendu; Halder, Arjun; Tharkar, Minakshi; Addicoat, Matthew; Ajithkumar, Thalasseril G.; Banerjee, Rahul (Journal of the American Chemical Society, 2020)
The induction of macro and mesopores into two-dimensional porous covalent organic frameworks (COFs) could enhance the exposure of the intrinsic micropores toward the pollutant environment, thereby, improving the performance. However, the challenge is to build a continuous hierarchically porous macro-architecture of crystalline organic materials in the bulk scale. In this regard, we have strategized a novel synthetic method to create hierarchically porous COF foams consisting of ordered micropores (2-2.2 nm) and disordered meso and macropores (50 nm to 200 mu m) as well as ordered macropores (1.5 mm to 2 cm). Herein, graphene oxide was used for creating disordered macro and mesopores in COF-GO foams. Considering the rheological features of the precursor hydrogel, we could integrate crystalline and porous COF-GO foams into self-supported three-dimensional (3D)-printed objects with the desired shapes and sizes. Therefore, we have engineered the 3D macro-architecture of COF-GO foams into complex geometries keeping their structural order and continuous porosity intact over a range of more than a million (10(-9) m to 10(-3) m). The interconnected 3D openings in these COF-GO foams further enhance the rapid and efficient uptake of organic and inorganic pollutants from water (>95% removal within 30 s). The abundant distribution of interconnected macroporous volume (55%) throughout the COF-GO foam matrix enhances the flow of water (1.13 x 10(-3) m.s(-1)) which results in efficient mass transport and adsorption.

Cobalt-manganese modified theophrastite phase of nickel hydroxide nanoflower arrays on nickel foam as a self-standing bifunctional electrode for overall water electrolysis - Kharabe, Geeta Pandurang; Illathvalappil, Rajith; Barik, Sidharth; Kanheerampockil, Fayis; Walko, Priyanka S.; Bhat, Suresh K.; Devi, R. Nandini; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2023)
Designing and developing self-supported electrodes for water electrolysis is attractive as compared to conventional catalyst-coated electrodes. Herein, a (Co0.3Mn0.1Ni0.6)(OH)(2)/NF nanocomposite is prepared by anchoring (Co0.3Mn0.1Ni0.6)(OH)(2)via simple one-pot hydrothermal synthesis on nickel foam. The presence of Mn induces the external electronic structure of Co(OH)(2), and this also improves the electrochemically active surface area (ECSA). These favor better accessibility of active sites and increased intrinsic activity for the OER and HER. (Co0.3Mn0.1Ni0.6)(OH)(2)/NF has shown promising electrochemical activity toward the OER and HER in a 1 M KOH electrolyte, with an overpotential of 270 mV for the OER and 163 mV for the HER to deliver 10 mA cm(-2) current density. The overall water splitting was performed by employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as both the cathode and anode by displaying a voltage of 1.62 V at 10 mA cm(-2), which is comparable to that extracted from a similar system based on the state-of-the-art Pt/C@NF cathode and RuO2@NF anode (1.60 V at 10 mA cm(-2)) standard electrode pair. Interestingly, at high current densities, the (Co0.3Mn0.1Ni0.6)(OH)(2)/NF//(Co0.3Mn0.1Ni0.6)(OH)(2)/NF system displayed better overall water splitting performance (1.78 V at 100 mA cm(-2)) compared to its Pt/C@NF//RuO2@NF (1.89 V at 100 mA cm(-2)) counterpart while displaying a stable output during the evolution period that lasted for 24 h. The amounts of H-2 and O-2 produced are estimated to be 701.2 and 358.6 mmol, respectively, at a time interval of 1 h; these amounts correspond to an similar to 1 : 2 ratio of O-2 and H-2, respectively. This study confirms the capability for employing (Co0.3Mn0.1Ni0.6)(OH)(2)/NF as a bi-functional and self-standing electrode for the realistic demonstrations of overall water splitting applications.

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery